The study on effect of waste water temperature on performance of heat pump water heater WTW - Nguyễn Văn Thái; Lê Minh Nhựt (Journal of Technical Education Science, 2017)
This paper presentss effect of waste water temperature on the performance (COP) of WTW (Water to Water) heat pump. The heat pump uses the waste water which is cooling water of air conditioning chiller system as the heat source. . The heat pump system is designed and installed at thermal workshop in Ho Chi Minh City University of Technology and Education. The electrical power of heat pump is 750W, the capacity of storage tank is 160 liters and the required temperature of hot water is 50 oC. Effect of waste water temperature on the COP of the heat pump has been studied both theoretically and experimentally. To evaluate the effect of temperature of the cooling water from the condenser of the water chiller system on performance (COP) of the heat pump, experiments are performed on different days. The experimental results show that when the cooling water temperature of condenser increases from 33 oC to 37 oC, the COP of hot water heat pump system also increases from 5,7 to 6,7.